Population spread in patchy landscapes under a strong Allee effect - Musgrave, Jeffrey; Girard, Alexandre; Lutscher, Frithjof (Université d'Ottawa | University of Ottawa, 2015)
Many species of invasive insects establish and spread in regions around the world, causing enormous eco- nomical and environmental damage, in particular in forests. Some of these insects are subject to an Allee effect whereby the population must surpass a certain threshold in order to establish. Recent studies have examined the possibility of exploiting an Allee effect to improve existing control strategies. Forests and most other ecosystems show natural spatial variation, and human activities frequently increase the degree of spatial heterogeneity. It is therefore imperative to understand how the interplay between this spatial varia- tion and individual movement behavior affects the overall speed of spread of an invasion. To this end, we study an integrodifference equation model in a patchy landscape and with Allee growth dynamics. Movement behavior of indi- viduals varies according to landscape quality. Our study focuses on how the speed of the resulting traveling periodic wave depends on the interaction between landscape frag- mentation, patch-dependent dispersal, and Allee population dynamics.
Keywords: Population spread; Allee effect; Patchy landscape